Development of Digital Comics Integrated with Pancasila Student Profiles in The Merdeka Curriculum to Enhance Narrative Text Comprehension - Rika Naisa'ada; Petra Kristi Mulyani (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2025)
This study investigates the development, feasibility, and effectiveness of Nafi Lala (Narasi Profil Pelajar Pancasila), a digital comic designed to enhance fourth-grade students' reading comprehension of narrative texts through the integration of Pancasila Student Profile dimensions in the Merdeka Curriculum. The research employs a research and development method, utilizing the ADDIE model, and collects data through interviews, questionnaires, pretests, posttests, and documentation. The study involves a small group of six students and a large group of 19 fourth-grade students in Semarang City, Central Java. Both qualitative and quantitative data analysis methods are applied, with qualitative data analyzed based on expert feedback and quantitative analysis involving normality tests, paired sample t-tests, and N-Gain analysis. The results show that the teaching module and content receive a score of 90%, while the media component achieves 92%, both categorized as "highly feasible". Student and teacher evaluations further support these findings, with feasibility ratings of 96.75% for the small group, 91.96% for the large group, and 92.11% for teachers. The effectiveness of the digital comic is demonstrated by posttest averages of 83.33 (small group) and 82.11 (large group), exceeding the minimum mastery threshold. The data meet the assumption of normality (p > 0.05), and paired t-tests confirm a significant improvement between pretest and posttest scores (p = 0.001 and p = 0.000, respectively). N-Gain scores are 63.64% (small group) and 69.28% (large group), both categorized as "moderately effective". These findings indicate that the digital comic integrated with Pancasila Student Profiles is feasible and effective in enhancing students